Kewenangan Kejaksaan dalam Melakukan Penahanan Terhadap Pelaku Tindak Pidana Ujaran Kebencian di Sosial Media - Louis Muda Adam Gesi Radja; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
Authority is what is called formal power, power comes from legislative power (given by law) or from executive administrative power. Authority, which usually consists of several powers, is power over a certain group of people or power over an area of ​​government. The purposes of this study are to analyze the arrangement of the prosecutor's authority in detaining the perpetrators of hate speech crimes on social media and the prosecutor's obstacles in detaining the perpetrators of hate speech crimes on social media. The research method applied in this research is normative legal research with a statutory and a conceptual approach. The technique of collecting legal materials is done by means of a literature study. The of used are primary, secondary, and tertiary sources of legal materials. After the legal material has been collected, it will then be processed and analyzed using the method of processing legal materials systematically and presented descriptively. The results of the study reveal that the prosecutor's authority is regulated in the criminal procedural law code, the prosecutor's authority law. Which includes several laws, among others, Law no. 16 of 2004 which regulates the prosecutor's office, so that from the law it can be ascertained about the rights and powers of the prosecutor so that law enforcers, especially the prosecutor's office, can make detentions in accordance with the rules that have been in force, so that there is no abuse of authority by law enforcers, especially prosecutors and as The prosecutor's office should be obliged to realize equality for all Indonesian citizens who are being entangled in criminal, civil and other cases.